Model Pendekatan SLPTT pada Daerah Sub Optimal/ Produktivitas Rendah (Studi Kasus Di Kabupaten Konawe Utara, Sulawesi Tenggara) - Suharno, Suharno (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2011)
Konawe Utara District is the new autonomous region built in 2008, separated of Konawe District. The total area of Konawe Utara is 487.786 ha, low land area is 1.829 ha covered 637 ha rural irrigation and 1.195 ha rainfall irrigation. Latest rice productivity is 3 t /ha wet paddy. The productivity is still low compared with other districts in Southeast Sulawesi. Since 2009, the government effort to increase rice productivity, one method is by Integrated Plant Management Field School (SLPTT). The resulting program in national level is achieved the rice productivity 5,91 %. Based on the experience, The AARD spill over the SLPTT Program to Konawe Utara by productivity targeted 15 % up. The result of SLPTT Program in Konawe Utara in 2010, rice productivity achieved is 4,5 t /ha, therefore another district is achieved productivity 8 t/ha. To know the problem of its, done the case study to several technologies which not optimally yet. Research result suggested that need approach model of SLPTT in low productivity region as Konawe Utara. Approach model of SLPTT does by learning of specific local technology component to farmer group and strengthening the farmer group activities and strengthening the seed producer.